Validity and reliability of the physiological and perceptual responses elicited during a novel treadmill-based Soccer Referee Simulation (SRS) - McEwan, G. P.; Unnithan, V. B.; Easton, C.; Glover, A. J.; Arthur, R. (Sport Sciences for Health, 2023)
Purpose This study explored the validity and reliability of the physiological and perceptual responses elicited during a novel treadmill-based Soccer Referee Simulation (SRS).